Antifungal potential of Enydra fluctuans extract for postharvest control of Colletotrichum siamense in dragon fruit - NGUYEN TRUNG TRUC; QUACH VAN CAO THI; DUONG THI CAM NHUNG (Smujo International, 2026)
Abstract. Truc NT, Thi QVC, Nhung DTC. 2026. Antifungal potential of Enydra fluctuans extract for postharvest control of Colletotrichum siamense in dragon fruit. Asian J Agric 10 (1): g100127. https://doi.org/10.13057/asianjagric/g100127. Pitaya, commonly known as red-fleshed dragon fruit, is rich in bioactive and nutritional compounds; however, its postharvest shelf life is limited due to high susceptibility to fungal diseases, particularly anthracnose caused by Colletotrichum spp. These infections significantly reduce fruit quality, shorten storage duration, and decrease economic value. This study investigated the antifungal efficacy of Whole Enydra fluctuans Phenolic Extract (WEPE) against postharvest pathogens of dragon fruit under in vitro and in vivo conditions. Fifteen fungal isolates were recovered from infected fruits, among which strain TL12 was identified as Colletotrichum siamense based on morphological characteristics and ITS rDNA sequencing. Pathogenicity tests confirmed Koch’s postulates, producing disease symptoms comparable to those observed in naturally infected fruits. To the best of our knowledge, this is the first report of C. siamense associated with postharvest anthracnose of dragon fruit in the studied region. WEPE obtained using ultrasound-assisted extraction with 45% ethanol exhibited the highest total phenolic content (18.26±1.49 mg GAE/g). In vitro assays demonstrated strong antifungal activity, with minimum inhibitory concentrations of 700 μg/mL for complete mycelial growth inhibition and 5000 μg/mL for spore germination inhibition. In vivo application of WEPE significantly suppressed anthracnose development on dragon fruit in a concentration-dependent manner. After 7 days of incubation, disease severity was reduced by approximately 30.4% and 55% at 700 and 5000 μg/mL, respectively, compared to the control. The results indicate that WEPE possesses strong antifungal potential against C. siamense and may be considered a promising natural agent for postharvest disease management in dragon fruit. However, these findings are based on short-term storage experiments under controlled laboratory conditions. Further research involving formulation optimization, extended storage evaluation, and field-scale validation is necessary before practical application in commercial postharvest systems.